Modern aspects of the development of information and control system in energetics - Chiflidzhanova-Hubenova, Zoya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In the present paper the energy systems are analyzed as an example of the so called large artificial systems. An example of a multilevel system has been considered which is associated with the problem of dispatching active power within the energy system. The advantages of multilevel control as compared to a centralized approach are shown below. Construction process of the so called integrated production systems aims at providing functional, infor-mation, software, and technical compatibility as well as efficiency of the individual subsystems. In terms of control each information management system, distinguished by a hierarchical structure, consists of three main levels: lowest – field level, the second one – operational and dispatching, and the third level – information level networks.